Effects of Heavy Metal Ions on Microbial Reductive Dechlorination of 1, 2-Dichloroethane and Tetrachloroethene - Wang, Jingjing; Li, Xiuying; Yan, Jun; Yang, Yi (Frontiers in Marine Science, 2022)
Microbial reductive dechlorination has been considered an effective process for the clean-up of organohalide-contaminated sites. Heavy metal ions are commonly present as co-contaminants in various organohalide-contaminated sites. To understand the impacts of heavy metal ions on the environmental fate of organohalides, we investigated the effects of Zn2+, Cu2+ and Cd2+ on reductive dechlorination of tetrachloroethene (PCE) and 1,2-dichloroethane (1,2-DCA) in sediment microcosms and transferred enrichment cultures. PCE and 1,2-DCA-dechlorinating enrichment cultures could be consecutively transferred in the presence of up to 10 mg/L Cu2+ or 10 mg/L Zn2+; by comparison, up to 50 mg/L Cd2+ had minor impacts on the microbial reductive dechlorination of PCE and 1,2-DCA. The inhibitory effects of tested heavy metal ions on microbial reductive dechlorination ranked in descending order are Zn2+, Cu2+, and Cd2+. Community profiling and principal component analysis indicate that the concentration and type of contaminants (e.g., heavy metal ions, organohalides) shaped the microbial community structure, an observation similar to a prior report. The enrichment of certain organohalide-respring bacteria (e.g., Dehalococcoides, Dehalogenimonas) during continuous transfers exposed to heavy metal ions suggests that they are capable of tolerating high concentrations of heavy metal ions. Our findings provide insights into the impacts of heavy metal ions on microbial reductive dechlorination and may be helpful for in situ bioremediation at sites contaminated with organohalides and heavy metals.